Amiodarone, Extreme AV Block and Pseudo-Pacemaker Syndrome: A Malady Caused By A Cure - Khairuman Fitrah Ananda Mamasta; Agustina Sianturi; Abigail Christine Sarumpaet (International Journal Labs, 2025)
Amiodarone is a potent antiarrhythmic that is used to treat supraventricular tachycardia (SVT). However, its substantial impact on atrioventricular (AV) nodal conduction can obscure or exacerbate underlying delays, resulting in rare conditions such as pseudo-pacemaker syndrome (PPMS). This syndrome is the result of an extreme prolongation of the PR interval, which results in AV dyssynchrony and hemodynamic compromise in the absence of an implanted device. A 25-year-old male presented with SVT, which was further complicated by hypokalemia. The case revealed a pre-existing AV nodal conduction delay. Therefore, we present the case. The patient transitioned to sinus rhythm after receiving amiodarone; however, they experienced a persistent and severe PR interval prolongation that exceeded 400 ms. The symptoms of vertigo and palpitations, which were consistent with PPMS, were induced by this severe conduction block and persisted for more than ten days, a reflection of the long half-life of amiodarone. This case concludes that amiodarone can dangerously exacerbate latent AV nodal disease in young adults, underscoring the necessity of recognizing PPMS as a clinical consequence of iatrogenic PR prolongation and emphasizing the need for cautious use and monitoring of antiarrhythmic drugs in patients with any evidence of conduction abnormalities.